True Monopolistic Competition as a Result of Imperfect Information - Wolinsky, Asher (Quarterly Journal of Economics, 1986)
The paper restates Hart's [1985a, 1985b] definition of large group monopolistic competition, distinguishes it from oligopolistic competition, and raises the ques-tion of whether there are reasonable circumstances that give rise to true monopo-listic competition as defined. The purpose is to show that consumers ' imperfect information may create conditions that will turn an otherwise oligopolistic market into a truly monopolistically competitive one. I.